Daur Hurūf Al-Jār Fi Taghyīr Ma’ani Al-Af’al Fi Kitab Al-‘Arabiyah Baina Yadaik (Al-Kitāb Ar-Rābi’) - Rosmala Ibrahim; Nofa Isman (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
لحروف الجر دور كبير في تغيير معاني بعض الأفعال، فيمكن لبعض الفعل من الأفعال معان عديدة بدخول حروف الجر فيها. لأجل ذلك، إن هذه الدراسة تهدف إلى معرفة دور حروف الجر في تغيير معاني الأفعال في كتاب العربية بين يديك (الكتاب الرابع) وعرض الاستفادة منها في تعليم اللغة العربية . وتسلك هذه الدراسة منهج الوصف التحليلي، وذلك بتتبع الأفعال التي تغيرت معانيها بتغير حروف الجر المتعاقبة بعدها في كتاب العربية بين يديك (الكتاب الرابع). أثبتت الدراسة على وجود الأفعال التي تغيرت معانيها بتغير حروف الجر المتعقبة بعدها في كتاب العربية بين يديك (الكتاب الرابع)، حيث هناك خمسون فعلا، ويتم ذكرها مع التحليل. Prepositions has a big role in changing the meanings of some verbs, so some verbs can have many meanings by entering prepositions into that. The purpose of this study is to knowing the role of prepositions in changing the meanings of verbs in the Arabic book baina yadaik (the fourth book) and offers to benefit from them. This study follows the analytical description method, by tracking the verbs whose meanings have changed by successive prepositions in the Arabic book Baina Yadaik (the fourth book). The study proved the existence of verbs whose meanings changed by following the prepositions in the Arabic book Baina Yadaik (the fourth book), and writer got fifty verbs and this is done with the analysis. The possibility of benefiting from it has also been shown to be a good use in Arabic language teaching for junior female students, especially at Ar-Raayah University. And that the teacher, indicating this study through dialogue and text, using many dictionaries. To understand the student about this study with giving them exercises.